Electrolyte, battery containing same and electric device
Patent Information
- Application Number
- CN202380045314.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-01-14
AI Technical Summary
Existing secondary batteries have problems with insufficient storage life and cycle performance during the cycle process. Especially in high-temperature environments, the battery expands and capacity decays quickly, which affects the service life.
An electrolyte is used, which contains a first additive with a polycyclic ester structure and SO2 and CO2 as the second additives. A dense inorganic-organic interface film is formed through copolymerization to improve the interface stability between the electrode pole piece and the electrolyte. , suppress the expansion and capacity fading of electrode materials, and introduce polymerization inhibitors into the electrolyte to reduce the risk of chemical reactions.
It significantly improves the cycle stability and storage life of secondary batteries, reduces the cycle performance degradation rate at high temperatures, and extends the service life of the battery.
Smart Images

Figure CN119318047A_ABST
Abstract
Description
Electrolyte, battery containing same and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery containing the electrolyte, and an electrical device. Background Art
[0002] In recent years, secondary batteries, due to their high energy density and recyclability, have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the rapid development and widespread application of secondary batteries, higher requirements have been placed on their cycling performance, storage life, and other performance characteristics.
[0003] Therefore, how to improve the cycle performance and storage life of secondary batteries is a technical problem that needs to be solved urgently.
[0004] Summary of the Invention
[0005] The embodiments of the present application provide an electrolyte, a battery containing the same, and an electrical device. The battery containing the electrolyte has improved cycle performance and storage life.
[0006] In a first aspect, an electrolyte is provided, comprising: a first additive, wherein the first additive comprises at least one of the compounds represented by formula (I) and formula (II):
[0007] Wherein, the values of x and y are each independently any natural number from 0 to 5, and x+y≥1, X1 and X2 include O or CH2 and X1 and X2 are not CH2 at the same time, R3, R4, R3' and R4' each independently include at least one of a saturated or unsaturated hydrocarbon group, and R5 and R6 each independently include at least one of a saturated or unsaturated hydrocarbon group with a carbon number of 1 to 6 and a single bond; a second additive, the second additive includes at least one of SO2 and CO2.
[0008] In an embodiment of the present application, the electrolyte includes a first additive and a second additive, and the first additive includes at least one of the compounds shown in formula (I) and formula (II). The compounds shown in formula (I) and formula (II) contain multiple cyclic ester structures, the compound molecular structure is large, the steric hindrance is large, and the solvation ability is weak. Therefore, the reaction activity at the electrode plate interface is low, the consumption rate in the electrolyte is slow, and the battery can continuously provide a film-forming material for repairing the interface film between the electrode plate and the electrolyte, thereby reducing the life decay rate in the middle and late stages of the battery cycle and improving the cycle stability and service life of the battery. Further, the compounds shown in formula (I) and formula (II) can simultaneously contain cyclic carbonate and cyclic sulfate and / or cyclic sulfonate structures, so that the first additive undergoes a copolymerization reaction in the electrolyte and participates in the film formation in the battery formation stage. The copolymer formed has the advantages of both polycarbonate polymer and polysulfate and / or polysulfonate polymer, the crystallinity of the copolymer is reduced, the toughness of the formed interface film is also improved, and the stability of the interface film is improved, thereby improving the storage life of the battery. At the same time, the electrolyte includes at least one of SO2 and CO2. SO2 and CO2 can change the breaking and bonding form of the first additive in the formation stage, inhibit the first additive from forming SO2 and CO2 in the formation stage, and instead form more inorganic-organic dense interface films containing sulfates, carbonates and polycarbonate-polysulfate / polysulfonate, that is, the copolymer contains more sulfate and carbonate structures, making the interface film denser, better preventing the co-embedding of other molecules in the electrolyte, avoiding the damage to the electrode material caused by the co-embedding of other molecules, and further improving the cycle stability and storage life of the battery.
[0009] In a possible implementation manner, the mass content of the second additive in the electrolyte is 10 ppm to 1000 ppm. Optionally, the mass content of the second additive in the electrolyte is 500 ppm to 800 ppm.
[0010] If the content of SO2 and CO2 is too little, it cannot effectively inhibit the first additive from forming SO2 and CO2 during the formation stage; if the content of SO2 and CO2 is too much, it will lead to excessive sulfate ions and carbonate ions in the electrolyte, which may combine with the metal ions produced by the electrode material, reducing the free metal ions in the electrolyte and causing the battery capacity to decay.
[0011] In a possible implementation manner, the mass content of the first additive in the electrolyte is 0.0001% to 10%. Optionally, the mass content of the first additive in the electrolyte is 0.01% to 5%.
[0012] If the content of the first additive in the electrolyte is too little, not enough copolymers can be formed to participate in film formation, affecting the stability of the interface film and causing instability in the interface between the electrode plate and the electrolyte; if the content of the first additive in the electrolyte is too high, the viscosity of the electrolyte will be too high, affecting the wetting of the electrolyte on the electrode plate and affecting the charge and discharge performance of the battery.
[0013] In one possible embodiment, R1 and R2 each independently include at least one of H, a halogen atom, a substituted or unsubstituted hydrocarbon group, and a group containing an unsaturated double bond or triple bond.
[0014] In the embodiments of the present application, by introducing halogen atoms into the compounds containing cyclic carbonate and cyclic sulfate and / or cyclic sulfonate structures of formula (I) and formula (II), the content of inorganic components in the compounds can be increased to improve the insulation of the interfacial film; by introducing hydrocarbon groups into the compounds, the stability of the compounds can be improved; by introducing unsaturated double bonds into the end groups of the compounds, the first additive has a multi-functional group structure, which makes it easier to form a cross-linked network structure during the film formation stage, which can better wrap the particle structure of the electrode material and inhibit the expansion of the electrode material, thereby further improving the cycle storage performance.
[0015] In one possible embodiment, R1 and R2 each independently include at least one of H, F, a linear or branched alkyl group having 1 to 3 carbon atoms, a linear perfluoro-substituted alkyl group having 1 to 3 carbon atoms, or a branched perfluoro-substituted alkyl group having 1 to 3 carbon atoms, and a group having 1 to 3 carbon atoms containing an unsaturated double bond.
[0016] In the embodiments of the present application, by adjusting the number of carbon atoms of the groups introduced into the compounds of formula (I) and formula (II), the structures of the compounds of formula (I) and formula (II) are optimized so that the first additive has suitable solubility and viscosity in the electrolyte, can better participate in film formation in the electrolyte, and improve the stability of the interface film between the electrode plate and the electrolyte.
[0017] In one possible embodiment, R5 and R6 each independently include at least one saturated or unsaturated hydrocarbon group having 1 to 3 carbon atoms.
[0018] In the embodiment of the present application, if the number of carbon atoms in the hydrocarbon structure between multiple ester groups is too large and the hydrocarbon structure is too long, it will affect the density of the electrode interface film formed by the first additive. By adjusting the number of carbon atoms in R5 and R6, the length of the hydrocarbon structure between multiple ester groups is made appropriate to form a tightly structured electrode interface film.
[0019] In one possible embodiment, the first additive includes at least one of the following substances:
[0020] In a possible implementation, the electrolyte further includes a third additive, and the third additive includes at least one of carbonate and sulfate.
[0021] During the battery formation stage, carbonates and sulfates form monomer active free radicals under electrochemical reactions, thereby increasing the reaction conversion rate of the first additive copolymerization to form a copolymer, making the initially formed copolymer interface film larger in molecular weight and denser, further improving the initial film quality.
[0022] In one possible implementation, the third additive includes at least one of vinylene carbonate, bisfluoroethylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, vinyl sulfate, and vinyl bissulfate.
[0023] In a possible implementation, the electrolyte further includes a polymerization inhibitor. Optionally, the polymerization inhibitor includes at least one of hydroquinone and 2,6-di-tert-butyl-p-cresol.
[0024] Hydroquinone and 2,6-di-tert-butyl-p-cresol are added to the electrolyte as inhibitors to reduce the risk of chemical reactions between substances in the electrolyte when they are in full contact during transportation of the battery, thereby reducing the risk of destruction of the components of the electrolyte.
[0025] In a possible implementation, the mass content of the polymerization inhibitor in the electrolyte is less than 20 ppm. Optionally, the mass content of the polymerization inhibitor in the electrolyte is less than 10 ppm.
[0026] The content of polymerization inhibitor in the electrolyte should not be too high, otherwise it will inhibit the copolymerization reaction of the first additive, affecting the film formation during the battery's formation stage, and preventing the formation of a stable interface film between the electrode and the electrolyte. Controlling the content of polymerization inhibitor improves the film quality during the battery's formation stage, thereby improving the battery's performance and service life.
[0027] In a possible implementation, the electrolyte further includes a solvent, and the relative dielectric constant of the solvent at 25° C. is greater than 2 and the viscosity is less than 2 mPa.s.
[0028] If the relative dielectric constant of the solvent in the electrolyte is too small or the viscosity is too high, the additive will be difficult to dissolve in the solvent.
[0029] In one possible embodiment, the solvent includes at least one of carbonate, carboxylate, ether, sulfone, fluorinated carbonate, fluorinated carboxylate, fluorinated ether, and fluorinated sulfone.
[0030] In a possible embodiment, the electrolyte further includes a metal salt, and the metal salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate. Optionally, the metal salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
[0031] In a possible implementation, the acidity of the electrolyte is less than 800 ppm.
[0032] If the acidity of the electrolyte is too high, the first additive may become unstable and degrade, making it difficult to form a copolymer and affecting the film quality.
[0033] In a second aspect, a battery is provided, comprising: the electrolyte according to the first aspect or any possible implementation of the first aspect.
[0034] In a third aspect, an electrical device is provided, comprising: the battery according to the second aspect or any possible implementation of the second aspect, wherein the battery is used to provide electrical energy.
[0035] In an embodiment of the present application, the electrolyte includes a first additive and a second additive, and the first additive includes at least one of the compounds shown in formula (I) and formula (II). The compounds shown in formula (I) and formula (II) contain multiple cyclic ester structures, the compound molecular structure is large, the steric hindrance is large, and the solvation ability is weak. Therefore, the reaction activity at the electrode plate interface is low, the consumption rate in the electrolyte is slow, and the battery can continuously provide a film-forming material for repairing the interface film between the electrode plate and the electrolyte, thereby reducing the life decay rate in the middle and late stages of the battery cycle and improving the cycle stability and service life of the battery. Further, the compounds shown in formula (I) and formula (II) can simultaneously contain cyclic carbonate and cyclic sulfate and / or cyclic sulfonate structures, so that the first additive undergoes a copolymerization reaction in the electrolyte and participates in the film formation in the battery formation stage. The copolymer formed has the advantages of both polycarbonate polymer and polysulfate polymer and / or polysulfonate. The crystallinity of the copolymer is reduced, the toughness of the formed interface film is also improved, and the stability of the interface film is improved, thereby improving the storage life of the battery. At the same time, the electrolyte includes at least one of SO2 and CO2. SO2 and CO2 can change the breaking and bonding form of the first additive in the formation stage, inhibit the first additive from forming SO2 and CO2 in the formation stage, and instead form more inorganic-organic dense interface films containing sulfates, carbonates and polycarbonate-polysulfate / polysulfonate, that is, the copolymer contains more sulfate and carbonate structures, making the interface film denser, better preventing the co-embedding of other molecules in the electrolyte, avoiding the damage to the electrode material caused by the co-embedding of other molecules, and further improving the cycle stability and storage life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0037] FIG1 is a schematic diagram of a battery cell disclosed in an embodiment of the present application;
[0038] FIG2 is a schematic diagram of the exploded structure of a battery cell disclosed in one embodiment of the present application;
[0039] FIG3 is a schematic diagram of the exploded structure of a battery disclosed in one embodiment of the present application;
[0040] FIG4 is a schematic diagram of an electrical device disclosed in an embodiment of the present application.
[0041] In the drawings, the drawings are not drawn to scale.
[0042] The reference numerals in the specific embodiment are as follows: battery 10 , box 11 , battery cell 20 , housing 21 , electrode assembly 22 , cover plate 23 . DETAILED DESCRIPTION
[0043] Below, the embodiments of the electrolyte, battery cells containing the electrolyte, batteries, and electrical devices of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] In the description of this application, it should be noted that, unless otherwise specified, "plurality" means more than two; terms such as "upper," "lower," "left," "right," "inner," and "outer" indicating directions or positional relationships are merely for the purpose of facilitating the description of this application and simplifying the description, and do not indicate or imply that the devices or components referred to must have a specific orientation, be constructed, or operate in a specific orientation. Therefore, they should not be construed as limiting this application. Furthermore, terms such as "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0045] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0046] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0048] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0049] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0051] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.
[0052] "Alkyl" refers to a monovalent saturated hydrocarbon group having one or more carbon atoms, optionally 1 to 18. For example, alkyl includes straight-chain and branched-chain alkyl groups, such as methyl (CH3-), ethyl (CH3CH2-), n-propyl (CH3CH2CH2-), isopropyl ((CH3)2CH-), n-butyl (CH3CH2CH2CH2-), isobutyl ((CH3)2CHCH2-), sec-butyl ((CH3)(CH3CH2)CH-), tert-butyl ((CH3)3C-), n-pentyl (CH3CH2CH2CH2CH2-), neopentyl ((CH3)3CCH2-), and the like.
[0053] "Perfluoro-substituted alkyl" refers to an alkyl group in which all hydrogen atoms in carbon-hydrogen bonds are replaced with fluorine atoms. Examples include perfluoro-substituted methyl (CF3-), perfluoro-substituted ethyl (CF3CF2-), perfluoro-substituted n-propyl (CF3CF2CF2-), and perfluoro-substituted isobutyl ((CF3)2CFCF2-).
[0054] An "unsaturated double bond" refers to a bond formed by two atoms sharing two pairs of electrons, such as a carbon-carbon double bond (C=C) or a carbon-oxygen double bond (C=O).
[0055] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are embedded in and released from the positive and negative electrodes. The electrolyte in the electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, prevents a short circuit while allowing ions to pass through, ensuring the normal electrochemical reactions in the secondary battery.
[0056] Secondary batteries can include lithium-ion batteries, sodium-ion batteries, magnesium-ion batteries, and others. This application uses lithium-ion batteries as an example. Lithium-ion batteries are a typical type of secondary battery. Because they rely on chemical reactions involving the intercalation and deintercalation of lithium ions between the positive and negative electrodes for charging and discharging, lithium-ion batteries are also known as rocking-chair batteries. During charging, lithium ions are released from the positive electrode, moved to the negative electrode, and then intercalated into the positive electrode. During discharge, lithium ions are released from the negative electrode, moved to the positive electrode, and then intercalated into the positive electrode.
[0057] In recent years, secondary batteries have been greatly developed and widely used in power tools, electronic products, electric vehicles, aerospace and other fields. At the same time, higher requirements are also placed on the volume capacity, energy density and cycle performance of secondary batteries.
[0058] During the initial charge of a secondary battery, the film-forming additives in the electrolyte are reduced to form a solid electrolyte interphase (SEI) film on the surface of the electrode. This SEI film prevents further decomposition of the non-aqueous organic solvent in the electrolyte and forms ion channels during subsequent charge and discharge cycles. However, as charge and discharge progress, the stability of the SEI film between the electrolyte and the electrode deteriorates, gradually breaking and then regenerating, causing continuous electrolyte consumption and affecting the cycle stability and service life of the secondary battery.
[0059] In view of this, the present application provides an electrolyte, wherein the first additive includes at least one of the compounds shown in formula (I) and formula (II). The compounds shown in formula (I) and formula (II) contain multiple cyclic ester structures, the compound molecular structure is large, the steric hindrance is large, and the solvation ability is weak. Therefore, the reaction activity at the electrode plate interface is low, the consumption rate in the electrolyte is slow, and the battery can continuously provide film-forming materials for repairing the interface film between the electrode plate and the electrolyte, thereby reducing the life decay rate in the middle and late stages of the battery cycle and improving the cycle stability and service life of the battery. Furthermore, the compounds shown in formula (I) and formula (II) can simultaneously contain cyclic carbonate and cyclic sulfate and / or cyclic sulfonate structures, so that the first additive undergoes a copolymerization reaction in the electrolyte and participates in the film formation in the battery formation stage. The copolymer formed has the advantages of both polycarbonate polymer and polysulfate and / or polysulfonate polymer, the crystallinity of the copolymer is reduced, the toughness of the formed interface film is also improved, and the stability of the interface film is improved, thereby improving the storage life of the battery. At the same time, the electrolyte includes at least one of SO2 and CO2. SO2 and CO2 can change the breaking and bonding form of the first additive in the formation stage, inhibit the first additive from forming SO2 and CO2 in the formation stage, and instead form more inorganic-organic dense interface films containing sulfates, carbonates and polycarbonate-polysulfate / polysulfonate, that is, the copolymer contains more sulfate and carbonate structures, making the interface film denser, better preventing the co-embedding of other molecules in the electrolyte, avoiding the damage to the electrode material caused by the co-embedding of other molecules, and further improving the cycle stability and storage life of the battery.
[0060] The following describes in detail several embodiments of the present application.
[0061] [Electrolyte]
[0062] The electrolyte acts as an ion conductor between the positive and negative electrodes. The electrolyte provided herein includes a first additive and a second additive. Specifically, the first additive includes at least one of the compounds represented by the following formula (I) and formula (II):
[0063] Wherein, the values of x and y are each independently any natural number from 0 to 5, and x+y≥1, X1 and X2 include O or CH2 and X1 and X2 are not CH2 at the same time, R3, R4, R3' and R4' each independently include at least one of a saturated or unsaturated hydrocarbon group, R5 and R6 each independently include at least one of a saturated or unsaturated hydrocarbon group with a carbon number of 1 to 6 and a single bond; the second additive includes at least one of SO2 and CO2.
[0064] Specifically, the compounds represented by formula (I) and formula (II) contain multiple cyclic ester structures, specifically, the compounds contain cyclic carbonates and cyclic sulfates and / or cyclic sulfonate structures. Cyclic carbonates have high dielectric constants and high ionic conductivity and can form a stable interface film on the electrode surface. Cyclic sulfates added to the electrolyte can inhibit the decrease in the initial capacity of the battery, increase the initial discharge capacity, reduce the expansion of the battery after high-temperature storage, and improve the battery's charge and discharge performance and cycle performance. Cyclic sulfonates added to the electrolyte can form a stable interface film on the electrode surface. In the electrolyte, the compounds of formula (I) and / or formula (II) undergo copolymerization reactions to form copolymers that have the advantages of both polycarbonate polymers and polysulfate polymers and / or polysulfonates.
[0065] Therefore, the electrolyte provided by the embodiment of the present application includes a first additive and a second additive, and the first additive includes at least one of the compounds shown in formula (I) and formula (II). The compounds shown in formula (I) and formula (II) contain multiple cyclic ester structures, the compound molecular structure is large, the steric hindrance is large, and the solvation ability is weak. Therefore, the reaction activity at the electrode plate interface is low, the consumption rate in the electrolyte is slow, and the battery can continuously provide a film-forming material for repairing the interface film between the electrode plate and the electrolyte, thereby reducing the life decay rate in the middle and late stages of the battery cycle and improving the cycle stability and service life of the battery. Further, the compounds shown in formula (I) and formula (II) can simultaneously contain cyclic carbonate and cyclic sulfate and / or cyclic sulfonate structures, so that the first additive undergoes a copolymerization reaction in the electrolyte and participates in the film formation in the battery formation stage. The copolymer formed has the advantages of both polycarbonate polymer and polysulfate polymer and / or polysulfonate polymer, the crystallinity of the copolymer is reduced, the toughness of the formed interface film is also improved, and the stability of the interface film is improved, thereby improving the storage life of the battery. At the same time, the electrolyte includes at least one of SO2 and CO2. SO2 and CO2 can change the breaking and bonding form of the first additive in the formation stage, inhibit the first additive from forming SO2 and CO2 in the formation stage, and instead form more inorganic-organic dense interface films containing sulfates, carbonates and polycarbonate-polysulfate / polysulfonate, that is, the copolymer contains more sulfate and carbonate structures, making the interface film denser, better preventing the co-embedding of other molecules in the electrolyte, avoiding the damage to the electrode material caused by the co-embedding of other molecules, and further improving the cycle stability and storage life of the battery.
[0066] Optionally, the value of x can be 0, 1, or 2, the value of y can be 0, 1, or 2, and x+y≥1. For example, x=0, y=1; x=1, y=1; x=2, y=1; x=0, y=2; x=1, y=2.
[0067] Optionally, in some embodiments, the mass content of the second additive in the electrolyte is 10 ppm to 1000 ppm. Optionally, the mass content of the second additive in the electrolyte is 500 ppm to 800 ppm.
[0068] Specifically, the mass content of the second additive in the electrolyte can be 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, or its value is within the range obtained by combining any two of the above values.
[0069] If the content of SO2 and CO2 is too little, it cannot effectively inhibit the first additive from forming SO2 and CO2 during the formation stage; if the content of SO2 and CO2 is too much, it will lead to excessive sulfate ions and carbonate ions in the electrolyte, which may combine with the metal ions produced by the electrode material, reducing the free metal ions in the electrolyte and affecting the performance of the battery.
[0070] Optionally, in some embodiments, the mass content of the first additive in the electrolyte is 0.0001% to 10%. Optionally, the mass content of the first additive in the electrolyte is 0.01% to 5%.
[0071] Specifically, the mass content of the first additive in the electrolyte can be 0.0001%, 0.0005%, 0.001%, 0.0015%, 0.002%, 0.0025%, 0.003%, 0.0035%, 0.004%, 0.0045%, 0.005%, 0.0055%, 0.006%, 0.0065%, 0.007%, 0.0075%, 0.008%, 0.0085%, 0.009% , 0.0095%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or its value is within the range obtained by combining any two of the above values.
[0072] If the content of the first additive in the electrolyte is too little, not enough copolymers can be formed to participate in film formation, affecting the stability of the interface film and causing instability in the interface between the electrode plate and the electrolyte; if the content of the first additive in the electrolyte is too high, the viscosity of the electrolyte will be too high, affecting the wetting of the electrolyte on the electrode plate and affecting the charge and discharge performance of the battery.
[0073] Alternatively, in some embodiments, R1 and R2 each independently include at least one of H, a halogen atom, a substituted or unsubstituted hydrocarbon group, and a group containing an unsaturated double bond or triple bond.
[0074] In the embodiments of the present application, by introducing halogen atoms into the compounds containing cyclic carbonate and cyclic sulfate and / or cyclic sulfonate structures of formula (I) and formula (II), the content of inorganic components in the compounds can be increased to improve the insulation of the interfacial film; by introducing hydrocarbon groups into the compounds, the stability of the compounds can be improved; by introducing unsaturated double bonds into the end groups of the compounds, the first additive has a multi-functional group structure, which makes it easier to form a cross-linked network structure during the film formation stage, which can better wrap the particle structure of the electrode material and inhibit the expansion of the electrode material, thereby further improving the cycle storage performance.
[0075] Optionally, in some embodiments, R1 and R2 each independently include at least one of H, F, a straight-chain alkyl group or a branched-chain alkyl group having 1 to 3 carbon atoms, a straight-chain perfluoro-substituted alkyl group or a branched perfluoro-substituted alkyl group having 1 to 3 carbon atoms, and a group having 1 to 3 carbon atoms containing an unsaturated double bond.
[0076] In the embodiments of the present application, by adjusting the number of carbon atoms of the groups introduced into the compounds of formula (I) and formula (II), the structures of the compounds of formula (I) and formula (II) are optimized so that the first additive has suitable solubility and viscosity in the electrolyte, can better participate in film formation in the electrolyte, and improve the stability of the interface film between the electrode plate and the electrolyte.
[0077] Alternatively, in some embodiments, R5 and R6 each independently include at least one saturated or unsaturated hydrocarbon group having 1 to 3 carbon atoms.
[0078] In the embodiment of the present application, if the number of carbon atoms in the hydrocarbon structure between multiple ester groups is too large and the hydrocarbon structure is too long, it will affect the density of the electrode interface film formed by the first additive. By adjusting the number of carbon atoms in R5 and R6, the length of the hydrocarbon structure between multiple ester groups is made appropriate to form a tightly structured electrode interface film.
[0079] Optionally, in some embodiments, the first additive includes at least one of the following substances:
[0080] It should be understood that the various compounds of formula (I) and formula (II) provided in the examples of the present application are merely examples and should not be construed as limiting the compounds of the present application.
[0081] In the embodiments of the present application, the introduction of fluorine atoms, which have the highest electronegativity among halogens, into the side chains of the compounds of formula (I) and formula (II) can further improve the stability and antioxidant properties of the compounds. Optionally, the groups R1 and R2 in the compounds of formula (I) and formula (II) are both fluorine atoms.
[0082] Optionally, in some embodiments, the electrolyte further includes a third additive, and the third additive includes at least one of carbonate and sulfate.
[0083] Specifically, the third additive includes at least one of vinylene carbonate (VC), bisfluoroethylene carbonate (DFEC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothioate (DTD), and dithiothioate (DTD-DTD).
[0084] It should be understood that the various compounds used as the third additive provided in the examples of the present application are merely examples and should not be construed as limiting the third additive of the present application.
[0085] During the battery formation stage, carbonates and sulfates form monomer active free radicals under electrochemical reactions, thereby increasing the reaction conversion rate of the first additive copolymerization to form a copolymer, making the initially formed copolymer interface film larger in molecular weight and denser, further improving the initial film quality.
[0086] Optionally, in some embodiments, the electrolyte further includes a polymerization inhibitor. Optionally, the polymerization inhibitor includes at least one of hydroquinone and 2,6-di-tert-butyl-p-cresol.
[0087] It should be understood that the various compounds used as polymerization inhibitors provided in the examples of the present application are merely examples and should not be construed as limiting the polymerization inhibitors of the present application.
[0088] Hydroquinone and 2,6-di-tert-butyl-p-cresol are added to the electrolyte as inhibitors to reduce the risk of chemical reactions between substances in the electrolyte when they are in full contact during transportation of the battery, thereby reducing the risk of destruction of the components of the electrolyte.
[0089] Optionally, in some embodiments, the mass content of the polymerization inhibitor in the electrolyte is less than 20 ppm. Optionally, the mass content of the polymerization inhibitor in the electrolyte is less than 10 ppm.
[0090] Optionally, the mass content of the polymerization inhibitor in the electrolyte can be 15 ppm, 10 ppm, 5 ppm, 4 ppm, 3 ppm, 2 ppm, or 1 ppm.
[0091] The content of polymerization inhibitor in the electrolyte should not be too high, otherwise it will inhibit the copolymerization reaction of the first additive, affecting the film formation during the battery's formation stage, and preventing the formation of a stable interface film between the electrode and the electrolyte. Controlling the content of polymerization inhibitor improves the film quality during the battery's formation stage, thereby improving the battery's performance and service life.
[0092] Optionally, in some embodiments, the electrolyte further includes a solvent, and the relative dielectric constant of the solvent at 25° C. is greater than 2 and the viscosity is less than 2 mPa.s.
[0093] Optionally, the relative dielectric constant of the solvent at 25° C. may be 3, 4, 5, or 6; and the viscosity of the solvent at 25° C. may be 1.5 mPa.s or 1 mPa.s.
[0094] If the relative dielectric constant of the solvent in the electrolyte is too small or the viscosity is too high, the additive will be difficult to dissolve in the solvent.
[0095] Optionally, in some embodiments, the solvent includes at least one of carbonate, carboxylate, ether, sulfone, fluorinated carbonate, fluorinated carboxylate, fluorinated ether, and fluorinated sulfone.
[0096] The solvent of the electrolyte is usually an organic solvent, such as carbonate, carboxylate, ether, sulfone, etc. The above organic solvents can improve the wettability of the electrolyte to the electrode plate, and have a high dielectric constant, reduce the impedance of the electrode plate embedded with active ions, improve the electrical conductivity, and improve the cycle performance of the battery.
[0097] Optionally, in some embodiments, the electrolyte further includes a metal salt.
[0098] Taking lithium-ion batteries as an example, the electrolyte of lithium-ion batteries includes lithium salts. Specifically, the lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), lithium tetrafluorooxalatophosphate (LiTFOP). Optionally, the lithium salts include at least one of LiPF6 and LiFSI. Metal salts dissolve in the electrolyte to produce free metal ions, which move directionally between the positive and negative electrodes of the battery to conduct electricity.
[0099] Secondary batteries may include lithium-ion batteries, sodium-ion batteries, magnesium-ion batteries, etc. Correspondingly, the metal salts may be lithium salts, sodium salts, magnesium salts, etc. It should be understood that the various metal salts provided in the embodiments of the present application are merely examples and should not be construed as limiting the metal salts of the present application.
[0100] Optionally, in some embodiments, the acidity of the electrolyte is less than 800 ppm.
[0101] Optionally, the acidity value of the electrolyte may be 700 ppm, 650 ppm, 600 ppm, 550 ppm, or 500 ppm.
[0102] Specifically, the acidity value of the electrolyte refers to the mass content of hydrofluoric acid (HF) in the electrolyte, and the free HF in the electrolyte can be titrated using a standard triethylamine solution.
[0103] If the acidity of the electrolyte is too high, the first additive may become unstable and degrade, making it difficult to form a copolymer and affecting the film quality.
[0104] The battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.
[0105] The present application also provides a battery cell. Typically, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery's charge and discharge process, active ions are embedded and released back and forth between the positive and negative electrode sheets. The electrolyte in the electrolyte acts as an ion conductor between the positive and negative electrode sheets. The separator is disposed between the positive and negative electrode sheets, primarily to prevent a short circuit between the positive and negative electrodes while allowing ions to pass through.
[0106] It should be understood that the "embedding" process described in this application refers to the process in which active ions are embedded in the positive electrode active material or the negative electrode active material due to an electrochemical reaction, and the "extraction" and "de-intercalation" processes described in this application refer to the process in which active ions are removed from the positive electrode active material or the negative electrode active material due to an electrochemical reaction.
[0107] [Positive electrode]
[0108] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0109] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0110] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0111] In some embodiments, the positive electrode active material may be a positive electrode active material for lithium ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates containing olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for lithium ion batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0112] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0113] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0114] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0115] [Negative electrode]
[0116] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0117] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0118] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0119] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0120] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0121] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0122] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0123] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0124] [Isolation film]
[0125] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0126] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0127] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0128] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0129] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0130] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape. For example, FIG1 shows a battery cell 20 having a square structure as an example.
[0131] In some embodiments, referring to Figure 2, the outer packaging may include a shell 21 and a cover plate 23. The shell 21 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 21 has an opening connected to the receiving cavity, and the cover plate 23 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 22 through a winding process or a lamination process. The electrode assembly 22 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 22. The number of electrode assemblies 22 contained in the battery cell 20 can be one or more, and those skilled in the art can select according to specific actual needs.
[0132] In some embodiments, the battery 10 may include multiple battery cells 20. For example, FIG3 is a schematic structural diagram of a battery 10 according to one embodiment of the present application. The battery 10 may include multiple battery cells 20. The battery 10 may also include a housing 11 having a hollow interior and housing the multiple battery cells 20. For example, the multiple battery cells 20 may be connected in parallel, in series, or in a mixed combination and then placed in the housing 11.
[0133] Optionally, the battery 10 may also include other structures, which will not be described in detail here. For example, the battery 10 may also include a busbar component, which is used to achieve electrical connection between multiple battery cells 20, such as parallel connection, series connection, or mixed connection. Specifically, the busbar component can achieve electrical connection between the battery cells 20 by connecting the electrode terminals of the battery cells 20. Furthermore, the busbar component can be fixed to the electrode terminals of the battery cells 20 by welding. The electrical energy of the multiple battery cells 20 can be further led out through the box 11 through a conductive mechanism. Optionally, the conductive mechanism may also belong to the busbar component.
[0134] The number of battery cells 20 can be set to any value based on different power requirements. Multiple battery cells 20 can be connected in series, parallel, or in a hybrid manner to achieve higher capacity or power. Since each battery 10 may include a large number of battery cells 20, for ease of installation, the battery cells 20 can be grouped, with each group of battery cells 20 forming a battery module. The number of battery cells 20 included in a battery module is not limited and can be set according to requirements. A battery can include multiple battery modules, which can be connected in series, parallel, or in a hybrid manner.
[0135] In addition, the present application also provides an electric device, which includes at least one of the battery cells, battery modules or batteries provided in the present application. The battery cells, battery modules or batteries can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0136] As the electrical device, a battery cell, a battery module or a battery can be selected according to its usage requirements.
[0137] Figure 4 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the battery cell, a battery or battery module can be used.
[0138] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be lightweight and thin, and may use a battery cell as a power source.
[0139] [Example]
[0140] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0141] (1) Preparation of compounds
[0142] Compound 1 Preparation:
[0143] Specifically, carbonyldiimidazole (1 mol) and acetonitrile as a solvent were added to a three-necked flask, and 1,2,3,4-tetrahydroxy-hexene (1.1 mol) was added. The mixture was reacted at a reaction temperature of 60-80°C for 2 hours. After the reaction was completed, the excess raw materials were precipitated and removed to obtain a reaction solution of product 1. 1 mol of sulfinyldiimidazole was added to the reaction solution of product 1, and the mixture was mixed at a reaction temperature of 20-40°C. After the mixing was completed, the materials were stirred at room temperature overnight; the reaction solution was concentrated, extracted with ethyl acetate, washed with water three times, and concentrated to obtain product 2. Product 2 (1 mol) was added to acetonitrile, and ruthenium trichloride (0.2 g) was added. The system was replaced with nitrogen. The reaction temperature was 15-25°C, and 10% sodium hypochlorite aqueous solution (1.1 eq) was added dropwise over 1 hour. After the addition was completed, the mixture was kept warm for 10 minutes and the liquids were separated. After the reaction was completed, the reaction solution was washed with saturated sodium sulfite aqueous solution until starch potassium iodide test paper did not turn blue, washed once with deionized water, and dried over anhydrous sodium sulfate. After filtration and concentration, the mixture was recrystallized from acetonitrile to obtain compound 1.
[0144] Compound 2 Preparation:
[0145] Specifically, carbonyldiimidazole (1 mol), acetonitrile as a solvent, and erythritol (1.1 mol) were added to a three-necked flask, and the mixture was reacted at a reaction temperature of 60-80°C for 2 hours. After the reaction, the excess raw materials were removed to obtain a reaction solution of product 1'. 1 mol of sulfinyldiimidazole was added to the reaction solution of product 1', and the mixture was mixed at a reaction temperature of 20-40°C. After the mixing was completed, the materials were stirred at room temperature overnight. The reaction solution was concentrated, extracted with ethyl acetate, washed with water three times, and concentrated to obtain product 2'. Product 2' (1 mol) was added to acetonitrile, followed by ruthenium trichloride (0.2 g). The system was purged with nitrogen. The reaction temperature was set at 15-25°C, and 10% aqueous sodium hypochlorite solution (1.1 eq) was added dropwise over 1 hour. After completion of the addition, the mixture was incubated for 10 minutes and the layers separated. After completion of the reaction, the reaction solution was washed with saturated aqueous sodium sulfite solution until starch potassium iodide paper did not turn blue. The mixture was then washed once with deionized water and dried over anhydrous sodium sulfate. After filtration and concentration, the mixture was recrystallized from acetonitrile to obtain product 3. Product 3 was added to a PFA reaction vessel, and fluorine / nitrogen gas (fluorine to nitrogen volume ratio of 3:7) was introduced at 50°C at a rate of 350 ml / min. After 0.5 hour of reaction, the compound was separated by column chromatography to obtain compound 2.
[0146] Compound 3 Preparation:
[0147] Specifically, in a three-necked flask, carbonyldiimidazole (2eq) and acetonitrile as solvent were added. The reaction was carried out at a temperature of 60-80°C for 2 hours. After the reaction was completed, the excess raw materials were precipitated and removed to obtain a reaction solution of product 4. 1 mol of sulfinyldiimidazole was added to the reaction solution of product 4, and the mixture was mixed at a reaction temperature of 20-40°C. After the materials were mixed, they were stirred at room temperature overnight. The reaction solution was concentrated, extracted with ethyl acetate, washed three times with water, and concentrated to obtain product 5. Product 5 (1 mol) was added to acetonitrile, ruthenium trichloride (0.2 g) was added, the system was purged with nitrogen, the reaction temperature was set at 15-25°C, and 10% sodium hypochlorite aqueous solution (1.1 eq) was added dropwise over 1 hour. After the addition was completed, the temperature was maintained for 10 minutes, and the liquids were separated. After the reaction was completed, the reaction solution was washed with saturated sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue, washed once with deionized water, and dried over anhydrous sodium sulfate. After filtration and concentration, the reaction solution was recrystallized from acetonitrile to obtain product 6. Product 6 was added to a PFA reaction tank, and fluorine / nitrogen gas (the volume ratio of fluorine and nitrogen was 3:7) was introduced at 50°C at a rate of 350 ml / min. After reacting for 0.5 h, the compound was separated by column chromatography to obtain compound 3.
[0148] Compound 4 Preparation:
[0149] Specifically, in a three-necked flask, add Acetonitrile was used as a solvent, triphosgene (1.1 mol) was added, and the reaction temperature was between 80-100°C for 2 hours. After the reaction, the excess raw material was removed and the product was concentrated under reduced pressure to obtain product 7. To the product 7 and acetonitrile solution, sulfinyldiimidazole (2 eq) was added, and the mixture was mixed at a reaction temperature of 20-40°C. After the mixing was completed, the materials were stirred at room temperature overnight; the reaction solution was concentrated, extracted with ethyl acetate, washed three times with water, and concentrated to obtain product 8. Product 8 (1 mol) was added to acetonitrile, ruthenium trichloride (0.2 g) was added, the system was purged with nitrogen, the reaction temperature was 15-25°C, and 10% sodium hypochlorite aqueous solution (2.2 eq) was added dropwise over 1 hour. After the addition was completed, the temperature was maintained for 10 minutes, and the liquids were separated; after the reaction, the reaction solution was washed with saturated sodium sulfite aqueous solution until the starch potassium iodide test paper did not turn blue, washed once with deionized water, and dried over anhydrous sodium sulfate; filtered, concentrated, and recrystallized from acetonitrile to obtain compound 4.
[0150] Compound 5 Preparation:
[0151] Specifically, based on the preparation of compound 4, compound 4 was added to a PFA reaction tank, and fluorine / nitrogen gas (the volume ratio of fluorine and nitrogen was 3:7) was introduced at 50°C at a rate of 350 ml / min. After reacting for 0.5 h, the compound was separated by column chromatography to obtain compound 5.
[0152] (2) Preparation of electrolyte: In an argon atmosphere glove box (H2O <0.1ppm, O2 <0.1ppm), the organic solvents EC and EMC were mixed evenly in a volume ratio of 3:7, 1M lithium hexafluorophosphate (LiPF6) was added and dissolved in the organic solvent, the first additive and the second additive were added and dissolved in the organic solvent, and stirred evenly to obtain the corresponding electrolyte.
[0153] (3) Preparation of positive electrode sheet: LiNi 0.5 Mn 0.38 Co 0.12 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 96:2:2, and are fully stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0154] (4) Preparation of negative electrode sheets: The active material artificial graphite, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water at a weight ratio of 96:1.5:1.5:1 and uniformly mixed with the solvent deionized water to prepare a negative electrode slurry; the negative electrode slurry is then uniformly coated on the negative electrode current collector copper foil, dried to obtain a negative electrode film, and then cold pressed and cut to obtain a negative electrode sheet.
[0155] (5) Preparation of isolation film: Conventional polypropylene film was used as the isolation film.
[0156] (6) Assembly of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator placed between the positive and negative electrode sheets to act as an isolater, and then wind them to obtain an electrode assembly; place the electrode assembly in a battery case, dry it, and inject the electrolyte, and then undergo formation, standing, and other processes to produce a lithium-ion battery.
[0157] [Comparative Example 1]
[0158] The first additive is compound 1. Electrolyte 1' containing compound 1 is prepared according to the above-mentioned method for preparing an electrolyte. The mass content of compound 1 in electrolyte 1' is 1%. Then, lithium-ion battery 1' containing electrolyte 1' is prepared according to the above-mentioned method for assembling a lithium-ion battery, corresponding to Example 1.
[0159] [Comparative Example 2]
[0160] The first additive is compound 2. According to the above method for preparing an electrolyte, an electrolyte 2' containing compound 2 is prepared. The mass content of compound 2 in the electrolyte 2' is 1%. Then, according to the above method for assembling a lithium ion battery, a lithium ion battery 2' containing electrolyte 2' is prepared, corresponding to Example 2.
[0161] [Comparative Example 3]
[0162] The first additive is compound 3. According to the above method for preparing an electrolyte, an electrolyte 3' containing compound 3 is prepared. The mass content of compound 3 in the electrolyte 3' is 1%. Then, according to the above method for assembling a lithium ion battery, a lithium ion battery 3' containing electrolyte 3' is prepared, corresponding to Example 3.
[0163] [Comparative Example 4]
[0164] The first additive is compound 4. According to the above method for preparing an electrolyte, an electrolyte 4' containing compound 4 is prepared. The mass content of compound 4 in the electrolyte 4' is 1%. Then, according to the above method for assembling a lithium ion battery, a lithium ion battery 4' containing electrolyte 4' is prepared, corresponding to Example 4.
[0165] [Comparative Example 5]
[0166] The first additive is compound 5. According to the above method for preparing an electrolyte, an electrolyte 5' containing compound 5 is prepared. The mass content of compound 5 in the electrolyte 5' is 1%. Then, according to the above method for assembling a lithium ion battery, a lithium ion battery 5' containing electrolyte 5' is prepared, corresponding to Example 5.
[0167] [Comparative Example 6-1]
[0168] Comparative Example 6-1 is different from Comparative Example 3 in that SO2 with a mass content of 5 ppm is added to Comparative Example 3 to prepare lithium-ion battery 6-1, which corresponds to Comparative Example 6-1.
[0169] [Comparative Example 6-2]
[0170] Comparative Example 6-2 is different from Comparative Example 3 in that, on the basis of Comparative Example 3, CO2 with a mass content of 5 ppm is added to prepare a lithium ion battery 6-2, which corresponds to Comparative Example 6-2.
[0171] [Comparative Example 7-1]
[0172] Comparative Example 7-1 is different from Comparative Example 3 in that SO2 with a mass content of 1200 ppm is added to Comparative Example 3 to prepare lithium-ion battery 7-1, which corresponds to Comparative Example 7-1.
[0173] [Comparative Example 7-2]
[0174] Comparative Example 7-2 is different from Comparative Example 3 in that, on the basis of Comparative Example 3, CO2 with a mass content of 1200 ppm is added to prepare lithium-ion battery 7-2, which corresponds to Comparative Example 7-2.
[0175] [Comparative Example 8]
[0176] The first additive is DTD. According to the above method for preparing an electrolyte, an electrolyte 8' containing DTD is prepared. The mass content of DTD in the electrolyte 8' is 1%. Then, according to the above method for assembling a lithium ion battery, a lithium ion battery 8' containing the electrolyte 8' is prepared, corresponding to Example 8.
[0177] [Comparative Example 9]
[0178] The first additive is VC. According to the above method for preparing an electrolyte, an electrolyte 9' containing VC is prepared. The mass content of VC in the electrolyte 9' is 1%. Then, according to the above method for assembling a lithium ion battery, a lithium ion battery 9' containing the electrolyte 9' is prepared, corresponding to Example 9.
[0179] [Comparative Example 10]
[0180] The first additive includes DTD and VC. According to the above-mentioned method for preparing an electrolyte, an electrolyte 10' containing DTD and VC is prepared, and the total mass content of DTD and VC in the electrolyte 10' is 1%. Then, according to the above-mentioned method for assembling a lithium-ion battery, a lithium-ion battery 10' containing the electrolyte 10' is prepared, corresponding to Example 10.
[0181] [Example 1]
[0182] The first additive was compound 1, and the second additive was SO2. An electrolyte 1 containing compound 1 and SO2 was prepared according to the above-described method for preparing an electrolyte. The mass content of compound 1 in electrolyte 1 was 1%, and the mass content of SO2 in electrolyte 1 was 100 ppm. A lithium-ion battery 1 containing electrolyte 1 was prepared according to the above-described method for assembling a lithium-ion battery, corresponding to Example 1.
[0183] [Example 2]
[0184] The difference between Example 2 and Example 1 is that the first additive is Compound 2, corresponding to Example 2.
[0185] [Example 3-1]
[0186] The difference between Example 3-1 and Example 1 is that the first additive is Compound 3, corresponding to Example 3-1.
[0187] [Example 3-2]
[0188] The difference between Example 3-2 and Example 3-1 is that the second additive is CO2, corresponding to Example 3-2.
[0189] [Example 4]
[0190] The first additive was compound 4, and the second additive was CO2. Electrolyte 4 containing compound 1 and CO2 was prepared according to the above-described method for preparing an electrolyte. The mass content of compound 4 in electrolyte 4 was 1%, and the mass content of CO2 in electrolyte 4 was 100 ppm. A lithium-ion battery 4 containing electrolyte 4 was prepared according to the above-described method for assembling a lithium-ion battery, corresponding to Example 4.
[0191] [Example 5]
[0192] The difference between Example 5 and Example 4 is that the first additive is Compound 5, corresponding to Example 5.
[0193] [Examples 6 and 7]
[0194] The difference between Examples 6 and 7 and Example 3-1 is that the mass content of compound 3 in the electrolyte is different. The mass content of compound 3 in the prepared electrolyte 6 and electrolyte 7 is 10% and 0.0001%, respectively. Then, according to the above-mentioned lithium-ion battery assembly method, lithium-ion battery 6 containing electrolyte 6 and lithium-ion battery 7 containing electrolyte 7 were prepared, corresponding to Examples 6 and 7, respectively.
[0195] [Examples 8-1, 9-1, 10-1, 11-1, 12-1 and 13-1]
[0196] The differences between Examples 8-1, 9-1, 10-1, 11-1, 12-1 and 13-1 and Example 3-1 are that the mass content of SO2 in the electrolyte is different. The mass contents of SO2 in the prepared electrolytes 8-1, 9-1, 10-1, 11-1, 12-1 and 13-1 are 10 ppm, 20 ppm, 300 ppm, 500 ppm, 800 ppm and 1000 ppm, respectively. The prepared lithium-ion batteries 8-1, 9-1, 10-1, 11-1, 12-1 and 13-1 correspond to Examples 8-1, 9-1, 10-1, 11-1, 12-1 and 13-1, respectively.
[0197] [Examples 8-2, 9-2, 10-2, 11-2, 12-2 and 13-2]
[0198] The differences between Examples 8-2, 9-2, 10-2, 11-2, 12-2 and 13-2 and Example 3-2 are that the mass content of CO2 in the electrolyte is different. The mass content of CO2 in the prepared electrolyte 8-2, electrolyte 9-2, electrolyte 10-2, electrolyte 11-2, electrolyte 12-2 and electrolyte 13-2 is 10ppm, 20ppm, 300ppm, 500ppm, 800ppm and 1000ppm, respectively. The prepared lithium-ion batteries 8-2, 9-2, 10-2, 11-2, 12-2 and 13-2 correspond to Examples 8-2, 9-2, 10-2, 11-2, 12-2 and 13-2, respectively.
[0199] [Example 14]
[0200] Example 14 is different from Example 9 in that, on the basis of Example 9, 5 ppm by mass of diphenol is added as a polymerization inhibitor to prepare a lithium ion battery 14, corresponding to Example 14.
[0201] [Example 15]
[0202] Example 15 is different from Example 10 in that, on the basis of Example 10, 1% by mass of bisfluoroethylene carbonate (DFEC) is added to prepare a lithium-ion battery 15, corresponding to Example 15.
[0203] [Example 16]
[0204] Example 16 is different from Example 9 in that, on the basis of Example 9, 25 ppm by mass of diphenol is added as a polymerization inhibitor to prepare a lithium ion battery 16, corresponding to Example 16.
[0205] The product parameters of different embodiments are detailed in Table 1.
[0206] Table 1: Product parameters of comparative examples and different embodiments
[0207] Next, the testing process of relevant parameters is explained.
[0208] 1. Storage performance test of lithium-ion batteries
[0209] At 25°C, charge the lithium-ion battery at a constant current of 0.5C to 4.5V, then charge it at a constant voltage of 4.5V until the current is less than 0.05C, then store the lithium-ion battery at 60°C, take it out every 5 days, fully charge it and then store it again. Stop testing when the capacity decays to 80%, and record the high-temperature storage time.
[0210] 2. Cycle performance test of lithium-ion batteries
[0211] At 45°C, a lithium-ion battery is charged at a constant current of 1C to 4.5V, then charged at a constant voltage of 4.5V until the current is less than 0.05C, and then discharged at a constant current of 1C to 2.8V. This charge and discharge process is considered one cycle. Repeat this cycle and calculate the number of cycles required for the lithium-ion capacity retention rate to reach 80%.
[0212] The capacity retention rate (%) of a lithium-ion battery after n cycles = (discharge capacity at the nth cycle / discharge capacity at the first cycle) × 100%.
[0213] The battery performance tests were performed on the prepared comparative examples 1-10 and examples 1-16 according to the above method. The results are shown in Table 2.
[0214] Table 2: Performance test results of comparative examples and different embodiments
[0215] From the comparison of the results of Comparative Examples 1 to 5 with those of Examples 1 to 5, it can be seen that by adding the compound provided in the present application comprising a cyclic carbonate and a cyclic sulfate structure and the second additive SO2 or CO2 to the electrolyte, the cycle performance of the lithium-ion battery is significantly improved, and the decay rate of the cycle performance of the lithium-ion battery at high temperature is significantly reduced, thereby increasing the service life of the lithium-ion battery and the storage life of the lithium-ion battery.
[0216] From the comparison of the results of Examples 1 to 5, it can be seen that by appropriately adding a cyclic carbonate or cyclic sulfate structure to the structure of the compound, the interfacial film formed by the copolymerization of the compound has better performance, which can further improve the cycle performance, service life and storage life of the lithium-ion battery.
[0217] From the comparison of the results of Example 3-1 with Examples 6 and 7, it can be seen that the mass content of the first additive in the electrolyte should not be too high or too low. By controlling the mass content of the first additive in the electrolyte within an appropriate range, the cycle stability, service life and storage life of the battery can be further improved.
[0218] From the comparison of the results of comparative examples 6-1, 6-2, 7-2 and 7-2 with those of examples 3-1, 3-2, 8-1 to 13-2, it can be seen that adding an appropriate amount of the second additive SO2 or CO2 to the electrolyte can promote the formation of an inorganic-organic dense interface film containing sulfate / carbonate and polycarbonate-polysulfate. The interface film is denser and better prevents the co-embedding of other molecules in the electrolyte, avoiding the damage to the electrode material caused by the co-embedding of other molecules, thereby improving the cycle performance, service life and storage life of the lithium-ion battery.
[0219] From the comparison of the results of Example 9-1 with Examples 14 and 16, it can be seen that an appropriate amount of inhibitor is added to the electrolyte to prevent the substances in the electrolyte from chemically reacting under full contact during the transportation of the battery and destroying the components of the electrolyte, thereby improving the cycle performance and service life of the lithium-ion battery; excessive inhibitor will affect the copolymerization reaction of the first additive, affect the film formation of the battery in the formation stage, and cannot form a stable interface film between the electrode plate and the electrolyte.
[0220] From the comparison of the results of Example 14 and Example 15, it can be seen that when DFEC is added to the electrolyte, DFEC forms monomer active free radicals under the electrochemical reaction, thereby improving the reaction conversion rate of the first additive copolymerization to form a copolymer, so that the molecular weight of the initially formed copolymer interface film is larger and denser, which can improve the cycle performance, service life and storage life of the lithium-ion battery.
[0221] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An electrolyte comprising: A first additive, wherein the first additive comprises at least one of the compounds represented by formula (I) and formula (II); Wherein, the values of x and y are each independently any natural number from 0 to 5, and x+y≥1, X1 and X2 include O or CH2 and X1 and X2 are not CH2 at the same time, R3, R4, R3' and R4' each independently include at least one of a saturated or unsaturated hydrocarbon group, and R5 and R6 each independently include at least one of a saturated or unsaturated hydrocarbon group having 1 to 6 carbon atoms and a single bond; The second additive includes at least one of SO2 and CO2.
2. The electrolyte according to claim 1, wherein The mass content of the second additive in the electrolyte is 10 ppm to 1000 ppm. Optionally, the mass content of the second additive in the electrolyte is 500 ppm to 800 ppm.
3. The electrolyte according to claim 1 or 2, wherein The mass content of the first additive in the electrolyte is 0.0001% to 10%. Optionally, the mass content of the first additive in the electrolyte is 0.01% to 5%.
4. The electrolyte according to any one of claims 1 to 3, wherein R1 and R2 each independently include at least one of H, a halogen atom, a substituted or unsubstituted hydrocarbon group, and a group containing an unsaturated double bond or triple bond.
5. The electrolyte according to claim 4, wherein R1 and R2 each independently include at least one of H, F, a linear or branched alkyl group having 1 to 3 carbon atoms, a linear perfluoro-substituted alkyl group having 1 to 3 carbon atoms, or a branched perfluoro-substituted alkyl group having 1 to 3 carbon atoms, and a group having 1 to 3 carbon atoms containing an unsaturated double bond.
6. The electrolyte according to any one of claims 1 to 5, wherein R5 and R6 each independently include at least one saturated or unsaturated hydrocarbon group having 1 to 3 carbon atoms.
7. The electrolyte according to any one of claims 1 to 6, wherein The first additive includes at least one of the following substances:
8. The electrolyte according to any one of claims 1 to 7, wherein The electrolyte further includes a third additive, and the third additive includes at least one of carbonate ester and sulfate ester.
9. The electrolyte according to claim 8, wherein The third additive includes at least one of vinylene carbonate, bisfluoroethylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, vinyl sulfate, and vinyl disulfate.
10. The electrolyte according to any one of claims 1 to 9, wherein The electrolyte further includes a polymerization inhibitor. Optionally, the polymerization inhibitor includes at least one of hydroquinone and 2,6-di-tert-butyl-p-cresol.
11. The electrolyte according to claim 10, wherein The mass content of the polymerization inhibitor in the electrolyte is less than 20 ppm. Optionally, the mass content of the polymerization inhibitor in the electrolyte is less than 10 ppm.
12. The electrolyte according to any one of claims 1 to 11, wherein The electrolyte also includes a solvent, wherein the relative dielectric constant of the solvent at 25° C. is greater than 2 and the viscosity is less than 2 mPa.s.
13. The electrolyte according to claim 12, wherein The solvent includes at least one of carbonate, carboxylate, ether, sulfone, fluorinated carbonate, fluorinated carboxylate, fluorinated ether, and fluorinated sulfone.
14. The electrolyte according to any one of claims 1 to 13, wherein The electrolyte also includes a metal salt, and the metal salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), and lithium tetrafluorooxalatophosphate. Optionally, the metal salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
15. The electrolyte according to any one of claims 1 to 14, wherein The acidity of the electrolyte is less than 800 ppm.
16. A battery comprising the electrolyte according to any one of claims 1 to 15.
17. An electrical device comprising the battery according to claim 16, wherein the battery is used to provide electrical energy.